2019
DOI: 10.1039/c8fo02013b
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin inhibits proliferation and induces apoptosis of human melanoma cells in vivo and in vitro by suppressing MMP-2 and MMP-9 through the PI3K/AKT pathway

Abstract: Since the incidence rate of malignant melanoma is increasing annually, development of drugs against melanoma cell metastasis has become more urgent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 32 publications
6
73
0
1
Order By: Relevance
“…Luteolin decreased the MMP-2 and MMP-9 expression and increased TIMP-1 and TIMP-2 expression. Inhibition of phosphorylated Akt1 and PI3K suggested that the reduction of MMP-2 and -9 expression was associated with PI3K/AKT pathway [ 61 ].…”
Section: Targeting Metastatic Cancermentioning
confidence: 99%
“…Luteolin decreased the MMP-2 and MMP-9 expression and increased TIMP-1 and TIMP-2 expression. Inhibition of phosphorylated Akt1 and PI3K suggested that the reduction of MMP-2 and -9 expression was associated with PI3K/AKT pathway [ 61 ].…”
Section: Targeting Metastatic Cancermentioning
confidence: 99%
“…Among these, a reduction of matrix metalloproteinase (MMP)-9 expression, a protein that is involved in extracellular matrix (ECM) degradation, was observed [119]. Moreover, MMP-2 can also be downregulated due to a decrease of phosphorylated AKT, and PI3K proteins [120]. Another target of luteolin is the catalytic subunit of telomerase, hTERT, that is downregulated such as its transcriptional inducer, c-myc, by a mechanism in which the cytoplasmic inactive form of NF-kB is stabilized.…”
Section: Luteolinmentioning
confidence: 99%
“…Recently, more and more evidence suggests that many Chinese medicinal herbs and their bioactive phytochemicals exhibit potential antitumor functions, providing an alternative therapy strategy for malignant melanoma treatment. For example, increasing studies have confirmed that Luteolin and parthenolide inhibit human melanoma cell proliferation and induce human melanoma cell apoptosis [3,4]. Polyphyllin I, a bioactive constituent extracted from Paris polyphylla, has extensive bioactivities and pharmaceutic activities.…”
Section: Introductionmentioning
confidence: 99%